2022
DOI: 10.1111/resp.14249
|View full text |Cite
|
Sign up to set email alerts
|

Periostin‐related progression of different types of experimental pulmonary hypertension: A role for M2 macrophage and FGF‐2 signalling

Abstract: Background and objective: Remodelling of pulmonary arteries (PA) contributes to the progression of pulmonary hypertension (PH). Periostin, a matricellular protein, has been reported to be involved in the development of PH. We examined the role of periostin in the pathogenesis of PH using different types of experimental PH. Methods: PH was induced by vascular endothelial growth factor receptor antagonist (Sugen5416) plus hypoxic exposure (SuHx) and venous injection of monocrotalinepyrrole (MCT-P) in wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…It can be induced by TGFβ1, 2 and 3, BMP2 and 4, VEGFA, CTGF, vitamin K and IL‐3, 4, 6 and 13 [ 6,8,9 ] and other inflammation cytokines. [ 39–41 ] POSTN could augment macrophage, HPASMCs, and HPMVECs migration; knockout POSTN attenuated the pulmonary arteries (PA) remodeling and accumulation of M2 macrophage to small PA. [ 42 ] In the present study, we also found that increased POSTN expression was accompanied by the upregulation of inflammatory factors; in contrast, knockout GMFβ reduced POSTN expression as well as the expression of inflammatory factors. Therefore, we supposed GMFβ may mediate POSTN through some inflammatory factors or some inflammatory pathways.…”
Section: Discussionsupporting
confidence: 70%
“…It can be induced by TGFβ1, 2 and 3, BMP2 and 4, VEGFA, CTGF, vitamin K and IL‐3, 4, 6 and 13 [ 6,8,9 ] and other inflammation cytokines. [ 39–41 ] POSTN could augment macrophage, HPASMCs, and HPMVECs migration; knockout POSTN attenuated the pulmonary arteries (PA) remodeling and accumulation of M2 macrophage to small PA. [ 42 ] In the present study, we also found that increased POSTN expression was accompanied by the upregulation of inflammatory factors; in contrast, knockout GMFβ reduced POSTN expression as well as the expression of inflammatory factors. Therefore, we supposed GMFβ may mediate POSTN through some inflammatory factors or some inflammatory pathways.…”
Section: Discussionsupporting
confidence: 70%
“…CASP1 [185], FOXP3 [186], SOCS1 [187], GATA6 [188], IRF7 [189], POSTN (periostin) [190], CYP19A1 [191], CD36 [192], LYN (LYN proto-oncogene, Src family tyrosine kinase) [193], CD4 [194], LEPR (leptin receptor) [195], AR (androgen receptor) [196], FOXO1 [197] and PON2 [198] are a potential biomarkers for the detection and prognosis of PCOS. Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216], Kušíková et al [217], Decharatchakul et al [218], Ahmed et al [219], Merklinger et al [220], Lei et al [146], Liu et al [221], Chen et al [222], Tan et al [223], Shi et al [224], Ikonnikova et al [225], Shimodaira et al [226], Pravenec et al [227], Zhang et al [228], Shah et al [229], Cicekliyurt and Dermenci [230], Ong et al [98], Nowzari et al [163], Kim et al [231], Bonafiglia et al [232], Selle et al [233],Yoo et al [234], Kasacka et al [235], Wang et al [236], Huang et al [237], Caceres et al [238], Lei et al [239], Lu et al [240], Cui et al [241], Xiao et al [242], Hiramatsu et al [243], Oliver et al [244], Grabowski et al [245], Zhu et al [246] and Li et al [247] demonstrated that the altered expression of CASP1, EDNRA (endothelin receptor type A), F2RL1, FOXP3, TIMP4, CD74, PLK1, TGFB1, GATA6, IRF7, IRF9, BGN (biglycan), C...…”
Section: Discussionmentioning
confidence: 99%
“…CX3CR1 [395], S100A12 [396], MPO (myeloperoxidase) [397], RXFP1 [398], S100A8 [399], CXCL11 [373], CBS (cystathionine beta-synthase) [400], WNT7A [401], BDNF (brain derived neurotrophic factor) [402], CXCL10 [403], CCL8 [404], FCGR3B [405], S100A9 [406], IL1B [407], CXCR2 [408], WNT3A [409], BMI1 [410], STC1 [411], ABCA3 [412], CD36 [413], TRIB3 [414], GPX3 [415], FGF2 [416], FASN (fatty acid synthase) [417], SHH (sonic hedgehog signaling molecule) [418], DACH1 [419], FGF9 [420], SLC7A11 [421], VIP (vasoactive intestinal peptide) [422], KL (klotho) [423], BMPR2 [424], APOA1 [425], LRRK2 [426], TLR3 [427], GATA3 [428], RSPO2 [429], CCR2 [430], NEK7 [431], BMPER (BMP binding endothelial regulator) [432], CAV1 [433], CR1 [434], TFPI (tissue factor pathway inhibitor) [435], AP1S2 [436], FOXJ1 [437], AQP5 [438], MUC16 [439] and MUC4 [440] could be used as a therapeutic target for IPF. CX3CR1 [441], S100A12 [442], PF4 [443], MPO (myeloperoxidase) [444], WNT7A [445], SLC6A4 [446], BDNF (brain derived neurotrophic factor) [447], CXCL10 [448], NEK7 [449], CYP1B1 [450], ABCA3 [451], TRIB3 [452], PCSK9 [453], FGF2 [454], ACKR4 [455], FASN (fatty acid synthase) [456], VIP (vasoactive intestinal peptide) [457], KL (klotho) [458], BMPR2 [459], APOA1 [323], TLR3 [460], CCR2 [461], TLR7 [462], CAV1 [463], WWC2 [464], TFPI (tissue factor pathway inhib...…”
Section: Discussionmentioning
confidence: 99%